Comment on article by Windle and Carvalho (2014)
The article by Windle and Carvalho introduces a fast update procedure for covariance matrices through the introduction of higher frequency sources of information for the underlying process, demonstrated with a financial application. This discussion focuses on outlining the assumptions and constraints around their use in financial applications, as well as an elicitation of some key choices made for comparison with traditional benchmarks, that may ultimately affect the results.